Trends in Antiseizure Medication Use: Implications for Practice and Clinical Care. (23rd August 2022) - Bensken, Wyatt P.; Sánchez Fernández, Iván
Abstract : One in 4 people who take prescription drugs in the United States have difficulties affording them. 1 It is no surprise that the American Academy of Neurology has identified the high price of prescription drugs for neurologic disorders, including epilepsy, a priority. 2 Most neurologists are familiar with the most obvious form of access challenges for a patient with epilepsy: they are unable to afford a medication. Commonly, health plans exclude newer antiseizure medications (ASMs) or cover them only after the patient has tried and failed several other ASMs, which the health plan considers first line. 3 Prior authorizations take up a tremendous amount of resources for health care providers. This form of restriction to access ASMs may be associated with delays in treatment. 4 Overlaid on this complexity is the changing landscape of ASMs including the dichotomy of generic vs brand name, with newer generations of ASMs improving safety and tolerability but not necessarily effectiveness. Neurologists can help address this problem as they manage other problems that jeopardize the health of their patients: by understanding the causes and identifying actionable solutions.